Association between glaucoma and risk of stroke: A systematic review and meta-analysis - Wang, Meng; Chen, Ni; Sun, Bai-chao; Guo, Chun-Bao; Zhang, Shuang; Huang, Ming-Jie; Zhou, Ben-Gang; Wang, Xiang-yu; Huang, Zheng-Biao (Frontiers in Neurology, 2023)
Background/objectives Recently, several studies explored the association between glaucoma and the risk of stroke, but these results were inconsistent. Therefore, we conducted a meta-analysis to examine this possible association. Methods We conducted a systematic literature search of PubMed, Embase, and Web of Science from inception until February 28, 2022. Random-effects meta-analysis was conducted by generic inverse variance method. Sensitivity and subgroup analyses were performed. The review protocol has been registered with PROSPERO (CRD42022312797). Results Seven studies (involving 362,267 participants) have been published from 2004 to 2017 and included in the meta-analysis. These studies included four retrospective cohort studies, two cross-sectional studies, and one case–control study. Meta-analysis of these data has shown that glaucoma was associated with an increased risk of stroke (OR = 1.94, 95% CI = 1.45–2.59). Most of the subgroup analyses demonstrated similar results. These findings were stable in sensitivity analyses. Conclusions We found that glaucoma was associated with an increased risk of stroke. The result suggests that patients with glaucoma need to be assessed the risk of stroke to reduce the incidence of stroke. To better explore the nature of any association, prospective studies that consider the stroke subtypes, sample size, district, and other confounding factors are needed.